Introducing a healthcare-assistive robot in primary care: a preliminary questionnaire survey - Tan, N. C.; Yusoff, Y.; Koot, D.; Lau, Q. C.; Lim, H.; Hui, T. F.; Cher, H. Y.; Tan, P. Y. A.; Koh, Y. L. E. (Frontiers in Robotics and AI, 2023)
HIRO is a health-assistive robot deployed in an outpatient primary care clinic to sanitize its premises, monitor people in its proximity for their temperature and donning of masks, and to usher them to service points. This study aimed to determine the acceptability, perceptions of safety and concerns among the patients, visitors and the polyclinic healthcare workers (HCW) on HIRO. A cross sectional questionnaire survey was conducted from March to April 2022 when HIRO was at Tampines Polyclinic in eastern Singapore. 170 multidisciplinary HCW serve approximately 1000 patients and visitors daily at this polyclinic. The sample size of 385 was computed using proportion of 0.5, 5% precision and 95% confidence interval. Research assistants administered an e-survey to gather demographic data and feedback from 300 patients/visitors and 85 HCW on their perceptions of HIRO using Likert scales. The participants watched a video on HIRO’s functionalities and were given the opportunity to directly interact with it. Descriptive statistics were performed and figures were presented in frequencies and percentages. The majority of participants viewed HIRO’s functionalities favourably: sanitizing (96.7%/91.2%); checking proper mask-donning (97%/89.4%); temperature-monitoring (97%/91.7%); ushering (91.7%/81.1%); perceived user-friendliness (93%/88.3%) and improvement in clinic experience (96%/94.2%). Minority of participants perceived harm from liquid disinfectant (29.6%/31.5%) and that its voice-annotated instructions may be upsetting (14%/24.8%). Most participants accepted HIRO’s deployment at the polyclinic and perceived it to be safe. HIRO used ultraviolet irradiation for sanitization during after-clinic hours instead of disinfectant due to its perceived harm.